Therapeutic drug monitoring of phenytoin needs vigilance: An individualized PD response is variable (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Therapeutic drug monitoring of Phenytoin is carried out to ensure effective and safe levels. Some of the factors complicating Phenytoin dosing include a narrow therapeutic window, high degree of protein binding, and non-linear pharmacokinetics. However, serum drug levels should only be taken when there is a clear indication to guide patient management. Scenarios where monitoring levels may be clinically useful include 1; establish an individual therapeutic concentration 2, aiding in diagnosis of clinical toxicity 3, assisting patient compliance and 4, guiding dosage adjustment in patients likely to have greater pharmacokinetic variability. The therapeutic range of Phenytoin is 10-20 microgram/ml. The study was carried out at a tertiary care where Neurology dept is well developed. This was a retrospective study a total number of samples of 2239 were included. Patients were taking only on monotherapy, Phenytoin. Samples were of trough levels and were taking the same dosage regimen. Patients were in the age range from 10 yrs. to 70 yrs. comprised 52.38% males and 46.62% females. 75% samples were in therapeutic range.